2012
DOI: 10.1111/j.1365-2567.2012.03592.x
|View full text |Cite
|
Sign up to set email alerts
|

Marked differences in CCR5 expression and activation levels in two South African populations

Abstract: Summary The chemokine receptor CCR5 is pivotal in determining an individual’s susceptibility to HIV‐1 infection and rate of disease progression. To establish whether population‐based differences exist in cell surface expression of CCR5 we evaluated the extent of CCR5 expression across all peripheral blood cell types in individuals from two populations, South African Africans (SAA) and South African Caucasians (SAC). Significant differences in CCR5 expression, both in number of CCR5 molecules per cell (density)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
(146 reference statements)
2
20
0
Order By: Relevance
“…None of the individuals included in this study expressed this mutant allele. We previously found marked differences in CCR5 haplotype prevalence and CCR5 expression in distinct South African populations, and that specific CCR5 haplotypes were associated with reduced CCR5 expression. CCR5 HHA haplotype has been suggested to predict slower HIV disease progression in HIV‐1‐infected individuals of African ancestry, and have the lowest transcriptional activity in vitro .…”
Section: Discussionsupporting
confidence: 73%
“…None of the individuals included in this study expressed this mutant allele. We previously found marked differences in CCR5 haplotype prevalence and CCR5 expression in distinct South African populations, and that specific CCR5 haplotypes were associated with reduced CCR5 expression. CCR5 HHA haplotype has been suggested to predict slower HIV disease progression in HIV‐1‐infected individuals of African ancestry, and have the lowest transcriptional activity in vitro .…”
Section: Discussionsupporting
confidence: 73%
“…Two PCR reactions were thus conducted for each sample, each with the common primer and one of the allele-specific primers which bind specifically to either the “wild type” or “mutant” allele. C T shift PCR assays have been successfully used for SNP genotyping in previous studies [17]. PCR conditions and ΔC T calculations were conducted as per Picton et al .…”
Section: Methodsmentioning
confidence: 99%
“…Population based studies reported the phenotype of the wild type gene as 75.56% in Rusia [32], 87.5% in Turkey [25], 98.21% in Cyprus Greek [32], 91.22% in Jordan [32], 97.16% in Syria [32], 97.96% in Kuwait [31], 100% in Yemen [25] being studies in Euro -Asia while 100% has been reported in Kenya [25] and Sudan [33]. The relatively higher frequency of the wild type gene of the CCR5 in African region is suggestive that the mutant variant (CCR5-Δ 32) is fairly recent in terms of human evolution [34,35]. The implication of the absence of the CCR5-Δ 32 gene in the studied population revealed a poor resistance to HIV and above all, underlined the fact that our HIV infected subjects are likely rapid progressors.…”
Section: Discussionmentioning
confidence: 99%